The Relationship between E-Book Material on Grouping Animals Based on Food Type and the Scientific Literacy Ability of Students in Elementary Schools - Nur Afifah Sulistiani; Wati Sukmawati (Postgraduate, University of Mataram, 2024)
The research aims to determine the level of validity and practicality as well as the partial relationship between e-book material on grouping animals based on food type and students' scientific literacy abilities at SDN Rambutan 02, East Jakarta. The research uses mixed research methods, with a quasi-experimental design model and a development model. The instrument trial involved 3 experts, namely media experts, material experts and language experts. Meanwhile, the group trial involved 45 students and 2 class teachers. Data analysis techniques include tabulation of expert validator questionnaire data and teacher and student response questionnaire data. This research shows that the level of validity and practicality of developing e-book-based science teaching materials is very good, and the results of the significance test of the relationship between e-book material on grouping animals based on food type and students' scientific literacy abilities show a t-count of 14.526 with a significance level of 0.000. So, it can be said that there is a significant relationship between the e-book material on grouping animals based on food type and the scientific literacy abilities of students at SDN Rambutan 02, East Jakarta.